2021
DOI: 10.1007/s00417-021-05186-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced macular vessel density in COVID-19 patients with and without associated thrombotic events using optical coherence tomography angiography

Abstract: Purpose Thrombotic events (TE) represent one of the major complications of SARS-CoV-2 infection. The objective is to evaluate vessel density (VD) and perfusion density (PD) by optical coherence tomography angiography (OCTA) in COVID-19 patients, and compare the findings with healthy controls. The secondary objective is to evaluate if there are differences in OCTA parameters between COVID-19 patients with and without associated TE. Methods Cross-sectional case-control study that included patients with laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 26 publications
1
29
3
Order By: Relevance
“…Recovered COVID-19 eyes showed a significant increase in peripapillary retinal nerve fibre (RNFL) thickness and superficial and deep macular VDs in parafoveal and perifoveal regions compared with healthy controls. This study contradicts the studies reporting a reduction in VD in COVID-19 eyes [ 37 , 40 , 42 ].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Recovered COVID-19 eyes showed a significant increase in peripapillary retinal nerve fibre (RNFL) thickness and superficial and deep macular VDs in parafoveal and perifoveal regions compared with healthy controls. This study contradicts the studies reporting a reduction in VD in COVID-19 eyes [ 37 , 40 , 42 ].…”
Section: Resultscontrasting
confidence: 99%
“…Guemes Villahoz et al [ 40 ] performed OCTA in patients 12 weeks after COVID-19 diagnosis. Ninety patients were included, 19 (20%) COVID-19 patients with associated thrombotic events, 47 (49.5%) COVID-19 patients without thrombotic events, and 29 (30.5%) healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…The eyes can be affected at many levels by SARS-CoV-2 as the virus has been isolated in the tears 3 , the conjunctiva 4 and even the retina 5 . Although no disease-specific lesions have been described neither in the anterior nor in the posterior segment of the eye many authors have reported the occurrence of direct or indirect signs of retinal circulation alterations in patients with COVID-19 ranging from retinal haemorrhages and cotton wool spots 6 , retinal vein occlusions 7 , 8 to a significant reduction in vascular density measured by optical coherence tomography angiography 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The ocular manifestation (conjunctivitis) is common in MIS-C associated with COVID-19 [7,8]. Retinal manifestations and SARS-Cov-2 detection in retina have also been reported [13][14][15]. Whether conjunctivitis is due to virus attack or related to an inflammatory response remains unknown.…”
Section: Introductionmentioning
confidence: 99%